1998
DOI: 10.1016/s0378-1097(98)00321-8
|View full text |Cite
|
Sign up to set email alerts
|

Human transferrin as a source of iron for Streptococcus intermedius

Abstract: Streptococcus intermedius is well known to produce severe infections in various areas of the body. In this study, we evaluated the ability of S. intermedius to utilise human transferrin as a source of iron and investigated the mechanism by which iron can be obtained from this plasma protein. Adding either ferrous sulfate or holotransferrin to an iron‐deficient culture medium allowed growth of S. intermedius. Cultivation of S. intermedius under an iron‐poor condition was associated with the over expression of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2000
2000
2011
2011

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 14 publications
(25 reference statements)
0
4
0
Order By: Relevance
“…The utilization of ferrous (Fe 2+ ) iron was thus considered as a factor in pathogenesis. Brochu et al (1998) demonstrated that ferrous sulfate stimulated the growth of S. intermedius (Brochu et al 1998). Our findings demonstrated that a concentration of ferrous sulfate below 10 mmol l )1 did not affect the growth of most bacterial strains tested.…”
mentioning
confidence: 51%
See 1 more Smart Citation
“…The utilization of ferrous (Fe 2+ ) iron was thus considered as a factor in pathogenesis. Brochu et al (1998) demonstrated that ferrous sulfate stimulated the growth of S. intermedius (Brochu et al 1998). Our findings demonstrated that a concentration of ferrous sulfate below 10 mmol l )1 did not affect the growth of most bacterial strains tested.…”
mentioning
confidence: 51%
“…The utilization of ferrous (Fe 2+ ) iron was thus considered as a factor in pathogenesis. Brochu et al. ( 1998) demonstrated that ferrous sulfate stimulated the growth of S. intermedius (Brochu et al.…”
Section: Discussionmentioning
confidence: 99%
“…The specific biological mechanism by which transferrin allele is related to differences in S. zooepidemicus infection in ponies is not known. It is possible that there is a direct link between pathogenesis of S. zooepidemicus infection and transferrin allele similar to that identified for S. intermedius by Brochu et al (1998). These authors demonstrated in vitro that S. intermedius was able to acquire iron in iron-restricted conditions by causing its release from transferrin by rapidly decreasing the pH of the culture medium.…”
Section: Transferrin Allelesmentioning
confidence: 65%
“…There have been several theoretical or empirical reasons why Fe has not been advised in populations where infections are endemic. First, experimental studies showed an increased bacterial growth when Fe was added to the culture medium (Andrews, 1998;Brochu et al 1998). Second, there were reports of increased intestinal parasitic infection during refeeding of refugees, although these studies were observational and there were confounding variables (Murray et al 1978).…”
Section: Ironmentioning
confidence: 99%